The political economy of sustainable development policy instruments and market mechanisms - Cadman, Timothy; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2015)
Since the Rio 'Earth' Summit of 1992, sustainable development has become the major policy response to tackling global environmental degradation, from climate change to loss of biodiversity and deforestation. Market instruments such as emissions trading, payments for ecosystem services and timber certification have become the main mechanisms for financing the sustainable management of the earth's natural resources. Yet how effective are they - and do they help the planet and developing countries, or merely uphold the economic status quo? This book investigates these important questions. Providing a comprehensive analysis and the latest research on sustainable development, the authors compare the divergent approaches to emissions trading. Included is a detailed investigation into illegal logging and the effectiveness of policy responses, with an evaluation of different forest certification schemes. Biodiversity offsets and environmental payments are also explored. Integral to the book are interviews and opinions of the key stakeholders in the political economy of sustainable development. This uniquely comprehensive analysis of the governance quality of different sustainable development mechanisms, unprecedented in its panorama of comparative case studies, is essential reading for all those in the policy, academic and non-governmental communities.
Introduction: The political economy of sustainable development -- 1. Protection of the atmosphere - CDM and REDD+ 47 -- 2. Combating deforestation I - FSC and PEFC -- 3. Combating deforestation II - FLEGT -- 4. Conservation of biological diversity - PES and BOM -- 5. Comparative analysis.
Includes index.
Keywords: Sustainable development; Electronic books